Pre-design model for redox flow battery design - Choi, Yun Young; Oh, Geunwoo; Choi, Jung-Il; Kim, Youngkwon; Kim, Ki Jae (Journal of mechanical science and technology, 2018)
Owing to complex configurations and the multi-physics phenomenon in a Redox flow battery (RFB), designing an RFB flow frame through Computational fluid dynamics (CFD) or experimentally requires high design costs. As an alternative approach, a compartment model can be applied to the design of an optimal RFB flow frame. In this study, we developed a pre-design model to estimate the parameters related to the energy efficiency of an RFB. A key factor of the proposed model is applying a classical pipe network theory and an electric circuit analogy to an RFB flow frame and stack. The pre-design model enables an estimation of the total pressure drop, flow rate distribution, and shunt current at the RFB cells or stack. Model-based estimates show good agreement with CFD and experimental results.